1. The problem statement, all variables and given/known data Solve the difference equation: an+2 - 5an+1 + 6an = 4n Subject to a0 = 0 & a1 = 1 2. Relevant equations an = Arn 3. The attempt at a solution I got two solutions for the first part for when it is homogeneous by substituting an = Arn into the equation and solving for r. an = A(3)n an = A(2)n I just don't know where to start for non-homogeneous. I tried an = B*4n and I got B*4n+2 -5B*4n+1 + 6B*4n = 4n but I don't know where to go from there.